Teachers’ Assessment Literacy in Multidisciplinary Learning in Finland – a Phenomenographic Approach to Teachers’ Perceptions - Ulla Hietamäki; Heidi Harju-Luukkainen; Minna Maunula (Nordic Studies in Education)
Assessment literacy is an essential part of a teacher’s pedagogical competence in Finland, but is an area of challenge and tensions. It develops during the teacher’s entire career, and is both context-independent and linked to internal factors. Multidisciplinary learning in schools promotes learning based on student interests, and stimulates active student participation through the exploration of real-world phenomena. Assessment during multidisciplinary learning requires teachers to utilise active assessment practices, including a wide range of assessment competencies to ensure that module assessment corresponds with curriculum aims, enables student participation, and is carried out in a varied and ethically sustainable way. This type of future-focused competence in assessment practices is a challenging area where teachers need more essential knowledge. This study examines Finnish primary school teachers’ perceptions of assessment literacy, in the context of multidisciplinary learning in schools. The data was collected using a phenomenographic approach, and was based on semi-structured interviews (n = 15). According to the findings, solidly competent assessment literacy safeguards the ethics of assessment, and contributes to professional development, the management of assessment knowledge, and the implementation of varied assessment. The results of this study contribute new insights to the debate on assessment literacy. The results can be used to develop primary education and increase understanding of the assessment literacy of teachers and student teachers in both national and international contexts.